The Foreign Trade of Greece and the EU during the Economic Crisis (2008) and the Health Crisis (2020): A Comparative Approach - Moskofidis, Anastasios; Magoulios, Georgios (Oeconomica Jadertina, 2022)
This paper examines the foreign trade of Greece compared to the foreign trade of EU28 during the Economic Crisis (2008) and the Health Crisis (2020). Based on the findings of relevant scientific literature, the quantitativ e data of external trade (exports, imports, trade balance) are recorded and analyzed methodologically. At the same time, the terms of trade and the degree of extroversion of Greek commerce compared to the corresponding figures of the EU28 during the period of the economic crisis (2008-2018) and the health crisis (2020-2021) are extracted. According to previous scientific literature in times of crisis, the volume of foreign trade at international, regional and national level is also bearing, among other financial figures. The economic crisis (2008) and the implemented harsh restrictive measures due to fiscal contraction resulted, among other consequences, in the reduction of income and internal demand, that the businesses confronted, strengthening their commercial extroversion, while for the same reasons imports decreased, resulting in an improvement in the trade balance, the terms of trade and the degree of commercial extroversion. Accordingly, from the current data, it seems that the exports of both Greece and the EU28 decreased to about the same extent during the period of the Health Crisis (2019-2020). As far as the external trade figures are concerned, it appears that the Greek degree of sensitivity to the effects of crises is greater than that of the EU28. Indeed, it appears that exports are less vulnerable to the effects of crises than imports. This behavior of Greek foreign trade can be explained by the sectoral composition of exports, in which the greatest relevance is attributed to the products with great elasticity of demand in terms of income, by the smaller size of enterprises and hence the limited access to commercial loans and external financing, but also by the lack of competitiveness of exported products in terms of added value, quality and price, compared to those of the EU28 and especially of the most developed countries. Suggestions for further research are to expand the period of the data taking into consideration the period of 2021 and solving dilemma how the new geopolitical crisis of Russia and Ukraine will affect the international trade relations, bonds and transactions.